PENGARUH SISTEM INFORMASI AKUNTANSI DAN AKTIVITAS SISTEM PENGENDALIAN INTERNAL TERHADAP PREVENSI FRAUD - wahyu cahyo nugroho; Erry Andhaniwati (Universitas Islam Negeri Alauddin Makassar, 2022)
This study aims to determine, test and prove empirically the effect of an accounting information system (AIS) on the implementation of fraud and the influence of internal control on the implementation of fraud. The type of approach in this study uses a quantitative approach. The sample used is from 8 cooperatives in Rungkut District, Surabaya City with primary data sources obtained directly from distributing questionnaires to 80 respondents.sampling technique used purposive sampling and data analysis using Partial Least Square (PLS) with a test tool in the form of SmartPLS 3. The results showed that the accounting information system had a positive and significant effect on fraud and internal control had a positive and significant effect on fraud prevention. Keywords: Accounting Information System, Internal Control, Fraud Prevention